Dissolved Organic Matter Controls Seasonal and Spatial Selenium Concentration Variability in Thaw Lakes across a Permafrost Gradient - Pokrovsky, Oleg; Bueno, Maïté; Manasypov, Rinat; Shirokova, Liudmila; Karlsson, Jan; Amouroux, David (Environmental Science & Technology, 2018)
International audience Little is known about the sources and processing of selenium, an important toxicant and essential micronutrient, within boreal and sub-arctic environments. Upon climate warming and permafrost thaw, the behavior of Se in northern peatlands becomes an issue of major concern, because a sizable amt. of Se can be emitted to the atm. from thawing soils and inland water surfaces and exported to downstream waters, thus impacting the Arctic biota. Working toward providing a first-order assessment of spatial and temporal variation of Se concn. in thermokarst waters of the largest frozen peatland in the world, we sampled thaw lakes and rivers across a 750-km latitudinal profile. This profile covered sporadic, discontinuous, and continuous permafrost regions of western Siberia Lowland (WSL), where we measured dissolved (<0.45 μm) Se concn. during spring (June), summer (August), and autumn (Sept.). We found max. Se concn. in the discontinuous permafrost zone. Considering all sampled lakes, Se exhibited linear relationship (R2 = 0.7 to 0.9, p < 0.05, n ≈ 70) with dissolved org. carbon (DOC) concn. during summer and autumn. Across the permafrost gradient, the lakes in discontinuous permafrost regions demonstrated stronger relationship with DOC and UV-absorbance compared to lakes in sporadic/isolated and continuous permafrost zones. Both seasonal and spatial features of Se distribution in thermokarst lakes and ponds suggest that Se is mainly released during thawing of frozen peat. Mobilization and immobilization of Se within peat-lake-river watersheds likely occurs as org. and organo-Fe, Al colloids, probably assocd. with reduced and elemental Se forms. The increase of active layer thickness may enhance leaching of Se in the form of org. complexes with arom. carbon from the deep horizons of the peat profile. Further, the northward shift of permafrost boundaries in WSL may sizably increase Se concn. in lakes of continuous permafrost zone.